Kronične levkemije - Glaser, Marjana (Medicinski razgledi, 2005)
Leukemias are malignant neoplasms of the hematopoietic system. They are characterized by the accumulation of a malignant clone of cells in the bone marrow and blood, which are afunctional. These cells are resistant to apoptosis, so they proliferate excessively and become accumulated in the bone marrow, leading to anemia, neutropenia and thrombocytopenia. Certain types of leukemia appear only during childhood, others exclusively in adults. Leukemias can be classified regarding the cell line to myeloid and lymphoid leukemias, an regarding their maturity and course of the disease to acute and chronic forms. The aim of this article is to present four chronic leukemias: chronic myeloid leukemia, which belongs to myeloproliferative diseases, and chronic lymphocytic leukemia, hairy cell leukemia and prolymphocytic leukemia, which are lymphoproliferative diseases.
Keywords: Leukemia, myeloid, chronic; Levkemija, mieloična, kronična; Levkemija, limfocitna, kronična; Leukemia, lymphocytic, chronic; Leukemia, hairy cell; Levkemija, dlakastocelična; Levkemija, prolimfocitna; Leukemia, prolymphocytic; levkemija; rak (medicina)